Samorządowi menadżerowie. Wybrane aspekty prawne i ekonomiczne w działalności wójta gminy po 1990 roku - Piasecki, Andrzej; Al. Azzawe, Thair (Polityka i Społeczeństwo, 2020)
The aim of this article is to analyze selected legal and economic aspects of the activities of a municipal administrator (wójt) in Poland. Based on the comparative method as well as on the latest expert studies in the field of law, administration, and economics, the author compares the changes that have taken place in the systemic status and in the activities of wójts. The most important legal acts regarding their powers have been examined. The influence of wójt on shaping the municipality’s budget and managing its assets have been analyzed. The effectiveness of management in the face of the diversity of Polish municipalities has also been compared. Empirical examples of effective public management by wójts have been used. The results of the local government elections in 2018 have also been analyzed as a test of the managerial competence of the wójts under consideration.